1999
DOI: 10.1175/1520-0493(1999)127<2419:tcksrf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Kinematic Structure Retrieved from Single-Doppler Radar Observations. Part I: Interpretation of Doppler Velocity Patterns and the GBVTD Technique

Abstract: Deducing the three-dimensional primary circulation of landfalling tropical cyclones (TCs) from single ground-based Doppler radar data remains a difficult task. The evolution and structure of landfalling TCs and their interactions with terrain are left uncharted due to the lack of dual-Doppler radar observations. Existing ground-based single-Doppler radar TC algorithms provide only qualitative information on axisymmetric TC center location and intensity. In order to improve understanding of the wind structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
140
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 19 publications
9
140
0
Order By: Relevance
“…Previous studies (Roux and Marks 1996;Lee and Marks 2000) have shown that the quality of the GBVTDretrieved winds critically depends on accurately knowing the circulation center. Since GrVTD is based on the same geometric relations as GBVTD, its performance also depends on the accuracy of TC center position.…”
Section: ) the Grvtd-simplex Center Findingmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies (Roux and Marks 1996;Lee and Marks 2000) have shown that the quality of the GBVTDretrieved winds critically depends on accurately knowing the circulation center. Since GrVTD is based on the same geometric relations as GBVTD, its performance also depends on the accuracy of TC center position.…”
Section: ) the Grvtd-simplex Center Findingmentioning
confidence: 99%
“…In practice, how to objectively determine a TC circulation center from V d becomes an important issue for GrVTD. Lee and Marks (2000) combined the ''simplex'' method (Nelder and Mead 1965) and the GBVTD-retrieved tangential circulations to form an elaborate center finding algorithm, named ''GBVTD-simplex,'' that can identify the TC center with reasonably good accuracy for both analytical and real TCs. They also noted that the estimated center discrepancy needs to be less than 5% RMW to keep the nominal error of the apparent wavenumber 1 less than 20%.…”
Section: ) the Grvtd-simplex Center Findingmentioning
confidence: 99%
See 3 more Smart Citations